Trends and determinants of contraceptive use among female adolescents in Ghana: Analysis of 2003-2014 Demographic and Health Surveys - Francis Appiah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Linus Baatiema; Edward Kwabena Ameyaw (Elsevier, 2020)
Introduction: Thirty percent (30%) of all deliveries in 2014 were recorded among adolescents in Ghana, whom contraceptive use has been found to be low. Our study, therefore, aimed to retrospectively look at the trends and determinants of contraceptive use (modern and traditional) among female adolescents in Ghana. Materials and methods: We used data from the 2003, 2008 and 2014 Ghana Demographic and Health Surveys. The sample for this study comprised sexually active female adolescents aged 15-19 for each of the rounds thereby resulting in a sample of 426 in 2003, 389 in 2008 and 726 in 2014. We calculated the proportion of adolescents using contraceptives (either traditional or modern) for each of the three surveys. We computed the use of contraceptives among adolescents and the type of contraceptives used with respect to their socio-demographic characteristics. Multinomial Logistic Regression was used to assess the determinants of contraceptive use at 95% confidence interval and Odds Ratios (OR) and p-values were reported. Results: Contraceptive use declined from 22.1% in 2003 to 20.4% in 2014. Adolescents who were married had lower odds [OR = 0.09, 95% CI = 0.03-0.96] of using traditional methods of contraception compared to those who were not married. Those who read newspapers at least once a week were more likely to utilize modern contraceptives [OR=1.84, CI = 1.05-4.78] compared to adolescents who did not read newspapers at all. Similarly, those who watched television at least once a week were more likely to use modern contraceptives than those who did not watch television at all [OR = 2.25, CI = 1.06-4.78]. Conclusion: These findings imply that intensifying educational messages on contraceptive use among adolescents using various newspapers and television stations to convey the messages and emphasizing the importance of using modern contraceptive is worthwhile.